2013
DOI: 10.1073/pnas.1220200110
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors interfering with dedifferentiation induce cell type-specific transcriptional profiles

Abstract: Transcription factors (TFs) are able to regulate differentiationrelated processes, including dedifferentiation and direct conversion, through the regulation of cell type-specific transcriptional profiles. However, the functional interactions between the TFs regulating different transcriptional profiles are not well understood. Here, we show that the TFs capable of inducing cell type-specific transcriptional profiles prevent the dedifferentiation induced by TFs for pluripotency. Of the large number of TFs expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 39 publications
(53 reference statements)
2
60
0
Order By: Relevance
“…The present finding that miR122 is downregulated by GRHL2 might provide an explanation for such mechanisms. Recently, it was demonstrated that key transcription factors defining neural lineage cells, including PAX6 and ETV6, inhibit dedifferentiation induced by OCT3/4 (POU5F1), SOX2, KLF4 and cMYC during reprograming (Hikichi et al, 2013). As we have previously demonstrated (Senga et al, 2012;Tanimizu et al, 2013), GRHL2 is a key transcription factor in inducing the cellular properties of mature cholangiocytes.…”
Section: Discussionmentioning
confidence: 76%
“…The present finding that miR122 is downregulated by GRHL2 might provide an explanation for such mechanisms. Recently, it was demonstrated that key transcription factors defining neural lineage cells, including PAX6 and ETV6, inhibit dedifferentiation induced by OCT3/4 (POU5F1), SOX2, KLF4 and cMYC during reprograming (Hikichi et al, 2013). As we have previously demonstrated (Senga et al, 2012;Tanimizu et al, 2013), GRHL2 is a key transcription factor in inducing the cellular properties of mature cholangiocytes.…”
Section: Discussionmentioning
confidence: 76%
“…Cellular differentiation, as well as reprogramming, results in global alterations of the transcriptional program and epigenetic modifications such as DNA methylation (18,19). On the other hand, misregulated differentiation can lead to aberrant transdifferentiation and abnormal cellular states, such as cancer (20)(21)(22).In this study our established in vitro circadian clock formation assay clearly shows that the constitutive expression of c-Myc and Dnmt1 −/− disrupted the development of the circadian clock. Global gene expression analysis reveals that 484 genes are identified as candidate factors correlating with emergence of circadian clock oscillation.…”
mentioning
confidence: 59%
“…Cellular differentiation, as well as reprogramming, results in global alterations of the transcriptional program and epigenetic modifications such as DNA methylation (18,19). On the other hand, misregulated differentiation can lead to aberrant transdifferentiation and abnormal cellular states, such as cancer (20)(21)(22).…”
mentioning
confidence: 99%
“…Indeed, depletion of the B cell-specifying TF Pax5 or ectopic expression of its antagonist CEB/P-alpha enables the reprogramming of terminally differentiated B cells 18 . Conversely, forced expression of lineage-specific TFs, in combination with OKSM, significantly impairs iPSC formation by sustaining a somatic gene expression program and preventing activation of pluripotency genes 19 . Together, these findings demonstrate that reprogramming TFs have to achieve two key tasks, namely the extinction of the somatic program, which is maintained by counteracting TFs, and the induction of a stable pluripotent state typical of ESCs.…”
Section: Mechanisms Of Induced Pluripotencymentioning
confidence: 99%